Bolaji & Bolaji, Information and Communication Technology Utilization for Managerial Planning Among Educational Administrators in Secondary Schools in Ilorin Metropolis - Tajudeen Oluwafemi Bolaji; Bolaji Hammed Olalekan (UII, 2022)
This study examines how secondary school administrators in the Ilorin Metropolis use ICT for managerial planning. The principal must effectively and efficiently organize, manage, and supervise the school's business for them to run successfully. This study's design is a survey-style descriptive study to determine how ICT affects principals' administrative performance. The population of this study consisted of 292 participants from all 75 public secondary schools in the Ilorin Metropolis. The instrument for data collection was a structured questionnaire titled